1973
DOI: 10.1113/jphysiol.1973.sp010332
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mammalian fast muscle: dynamic and biochemical properties correlated

Abstract: SUMMARY1. The isometric properties and related biochemical properties of a developing rat fast muscle (extensor digitorum longus, EDL) have been determined during the 21 days after birth.2. At birth the maximum rate of rise of tension in a tetanus, a measure of speed of contraction, is slow; it begins to increase only after the 5th day and reaches adult values by 21 days. 3. The increase in actomyosin ATPase activity of the rat EDL correlates closely (P < 0.001) with the changes in the maximum rate of rise dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
1
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 16 publications
2
21
1
1
Order By: Relevance
“…They are also consistent with the presumed role of these myosins in the adaptation of neonatal muscles to demanding physiological functions including breathing (66). MyHC-Perinatal displays a slightly higher ATPase profile than MyHC-Embryonic, which correlates well the increased enzymatic activity in the developing muscles of chickens and rats when MyHC-Perinatal replaces MyHC-Embryonic (32).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…They are also consistent with the presumed role of these myosins in the adaptation of neonatal muscles to demanding physiological functions including breathing (66). MyHC-Perinatal displays a slightly higher ATPase profile than MyHC-Embryonic, which correlates well the increased enzymatic activity in the developing muscles of chickens and rats when MyHC-Perinatal replaces MyHC-Embryonic (32).…”
Section: Discussionsupporting
confidence: 78%
“…The ATPase activities of the developmental and the MyHC-Extraocular isoforms are less clear due to their heterogeneous expression with other isoforms. Preliminary work suggests the developmental myosins have low ATPase activities (31,32), while MyHCExtraocular is thought to be a very fast myosin (22,29,33). All of this evidence points to the conclusion that myosin isoform expression patterns are a likely mechanism for the specialization of muscles to perform specific tasks.…”
mentioning
confidence: 99%
“…Significant increases in Pt values were already reported when comparing prepubertal to postpubertal children (1-4). The higher Pt values are classically considered to reflect different peripheral mechanisms which could accompany growth: (i) increase in muscle fibre diameter until growth is completed (18); (ii) increase in the number of sarcomeres with relation to muscle fibers size (19,20); (iii) changes in the activity of myosin ATPase, which highly contributes to contractile characteristics, and which is higher for an adult muscle than for a child muscle (21). Because peak torque related to calf circumference increases with age, it can be proposed that for humans, ATPase activity also increases with the age of the child.…”
mentioning
confidence: 99%
“…The maximum rate of isometric tension generation has, until recently, been taken to correlate with maximal shortening velocity (Close, 1972;Drachman & Johnston, 1973). Recently, however, it has been suggested that the two parameters may not necessarily change in parallel.…”
Section: Resultsmentioning
confidence: 99%